Analysis of Changes in Atmospheric CO2 Emissions Using Prophet Facebook - Primandari, Arum Handini; Thalib, Achmad Kurniansyah; Kesumawati, Ayundyah (Universitas Islam Indonesia, 2022)
CO2 emissions have been an environmental issue for decades. The trigger for the increasing concentration of CO2 in the atmosphere is the growth of industries related to burning fossil fuels for coal, natural gas, and petroleum. For nearly a century, several attempts have been made to suppress the rapid growth of CO2 . This study uses daily atmospheric CO2 levels observed in Mauna Loa laboratories. The method used is a Prophet that can handle seasonality and mark the change points. Almost 20% of data was missing value, which was then imputed using spline interpolation. Based on the analysis results, CO2 levels have an upward trend throughout the year and seasonality. There is no point of change in the last ten years that shows a decrease in CO2 levels. Using forward chaining cross-validation evaluation and error measurement, the prophet model can follow the pattern of CO2 levels well. The average RMSE value is less than 2.0, with an MAPE value bellow 0.5%.